2015
DOI: 10.1210/en.2014-1650
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Promotes Renal Tubular Cell Survival in Male Diabetic Rats: Implications for Ligand Inactivation in the Human Kidney

Abstract: Binding of the receptor CXCR4 to its ligand stromal cell-derived factor 1 (SDF-1) promotes cell survival and is under the influence of a number of regulatory processes including enzymatic ligand inactivation by endopeptidases such as matrix metalloproteinase 9 (MMP-9). In light of the pivotal role that the SDF-1/CXCR4 axis plays in renal development and in the pathological growth of renal cells, we explored the function of this pathway in diabetic rats and in biopsies from patients with diabetic nephropathy, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…A study in the kidney after ischemic acute renal injury showed the expression of CXCR4 in tubular cells (Togel et al, 2005). Siddiqi et al (2015) also confirmed that CXCR4 mRNA and protein increased approximately two to three-folds in the kidneys of diabetic rats compared with control. In addition, the expression of CXCR4 in NRK-52E cells was confirmed by immunoblotting.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A study in the kidney after ischemic acute renal injury showed the expression of CXCR4 in tubular cells (Togel et al, 2005). Siddiqi et al (2015) also confirmed that CXCR4 mRNA and protein increased approximately two to three-folds in the kidneys of diabetic rats compared with control. In addition, the expression of CXCR4 in NRK-52E cells was confirmed by immunoblotting.…”
Section: Discussionmentioning
confidence: 62%
“…High glucose increased the expression of TLR2/4 in HK-2 cells and played an important role in diabetic nephropathy (Mudaliar et al, 2013). CXCR4 is receptor of Stromal cell-derived factor-1 (SDF-1), which contributes to chemotaxis, activation, and homeostasis of many cells (Siddiqi et al, 2015). HMGB1 promoted recruitment of inflammatory cells to damaged tissues by forming a complex with CXCL12 and signaling through CXCR4 (Schiraldi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 CXCL12 is in addition elevated after ischaemic reperfusion injury protecting tubular epithelial cells as shown by Stokman et al 36 in animal models using antisense oligonucleotides against CXCL12. 35 CXCL12 is in addition elevated after ischaemic reperfusion injury protecting tubular epithelial cells as shown by Stokman et al 36 in animal models using antisense oligonucleotides against CXCL12.…”
Section: Stressmentioning
confidence: 88%
“…Binding of CXCL12, also known as stromal cell-derived factor 1 (SDF-1), to the chemokine receptor 4 (CXCR4) represents another mechanism counteracting apoptosis of renal cells. 35 CXCL12 is in addition elevated after ischaemic reperfusion injury protecting tubular epithelial cells as shown by Stokman et al 36 in animal models using antisense oligonucleotides against CXCL12. CCR7 is linked to CXCR4 and CXCL12 in the protein-protein interaction network and also reported to be involved in antiapoptotic processes in mesangial cells.…”
Section: Stressmentioning
confidence: 92%